Analysis of The Influence of Leadership Style, Workload and Work Stress on Employee Performance: Empirical Study from The MATSC Branch of Aviation Navigation Service Provider Institution - Amal A. R, Chaerul; Daga, Rosnaini; Samad, Abdul (Manunggal Halim Jaya, 2025)
This study aims to determine and analyze the influence of leadership style variables, workload, and work stress on employee performance at the MATSC branch of an aviation navigation service provider institution. The analysis tool used in this study is data analysis using SPSS. The population in this study was all telecommunications technician employees of the MATSC branch of the aviation navigation service provider institution, totaling 94 employees. The results of the study indicate that: (1) Leadership style has a positive and significant effect on employee performance at The MATSC branch of aviation navigation service provider institution; (2) Workload has a negative but insignificant effect on employee performance at The MATSC branch of aviation navigation service provider institution; (3) Work stress has a negative but insignificant effect on employee performance at The MATSC branch of aviation navigation service provider institution; (4) Leadership style, workload and work stress simultaneously have a significant effect on employee performance at The MATSC branch of aviation navigation service provider institution.